Breaking Barriers: Strategies for Developing Women Leaders in Public Service - Ganis Setyaningrum; Juansih Juansih; Fendy Suhariadi; Ian Firstian Aldhi (Dinasti Publisher, 2024)
This article offers a comprehensive perspective on leadership development by addressing the distinctive requirements of women in public organizations. The opportunities and constraints in each of the seven categories of leadership development practices are analyzed for women. In order to facilitate the advancement of women's leadership development, this article provides advisory recommendations for human resource professionals and consulting psychologists who are focused on female clients and organizational practices. Ultimately, this article explores the research's overarching themes and their implications for the development of leadership and women. Organizations establish effective leadership development systems for women. When women are informed about the leadership development practices within their organizations, they are more likely to develop stronger organizational connections, which may result in a greater level of organizational commitment.